Systemic Immune-Inflammation Index Is a Prognostic Predictor in Patients with Intrahepatic Cholangiocarcinoma Undergoing Liver Transplantation - Ao Ren; Zhongqiu Li; Pengrui Cheng; Xuzhi Zhang; Ronghai Deng; Yi Ma (Mediators of Inflammation)
Background. It was reported that systemic immune inflammation index (SII) was related to poor prognosis in a variety of cancers. We aimed to investigate the ability of the prognostic predictors of SII in patients with intrahepatic cholangiocarcinoma (iCCA) undergoing liver transplantation (LT). Methods. The 28 iCCA patients who underwent LT at our hospital between 2013 and 2018 were reviewed. Kaplan–Meier survival curves and Cox regression analyses were used to evaluate the prognostic significance of SII. Patients were divided into the high and low SII groups according to the cut-off value. Results. The 1-, 3-, and 5-year OS rates were significantly lower in the high SII group (85.7%, 28.6%, and 21.4%, respectively) than in the low SII group (92.9%, 71.4%, and 57.2%, respectively; P=0.009). The 1-, 3-, and 5-year RFS rates were, respectively, 57.1%, 32.7%, and 21.8% in the high SII group and 85.7%, 61.1%, and 61.1% in the low SII group (P=0.021). SII≥447.48×109/L (HR 0.273, 95% CI 0.082–0.908; P=0.034) was an independent prognostic factor for OS. Conclusions. Our results showed that SII can be used to predict the survival of patients with iCCA who undergo LT.